Broken links, enduring ties : American adoption across race, cClass, and nation - Seligmann, Linda J., 1954- (Stanford University Press, 2013)
Family-making in America is in a state of flux-the ways people compose their families is changing, including those who choose to adopt. Broken Links, Enduring Ties is a groundbreaking comparative investigation of transnational and interracial adoptions in America. Linda Seligmann uncovers the impact of these adoptions over the last twenty years on the ideologies and cultural assumptions that Americans hold about families and how they are constituted. Seligmann explores whether or not new kinds of families and communities are emerging as a result of these adoptions, providing a compelling narrative on how adoptive families thrive and struggle to create lasting ties.